Nanoparticle–allergen complexes for allergen immunotherapy - Di Felice G (Dove Medical Press, 2017)
Gabriella Di Felice,1 Paolo Colombo2 1National Center for Drug Research and Evaluation, Istituto Superiore di Sanità, Rome, 2Institute of Biomedicine and Molecular Immunology, National Research Council, Palermo, Italy Abstract: Allergen-specific immunotherapy was introduced in clinical settings more than 100 years ago. It remains the only curative approach to treating allergic disorders that ameliorates symptoms, reduces medication costs, and blocks the onset of new sensitizations. Despite this clinical evidence and knowledge of some immunological mechanisms, there remain some open questions regarding the safety and efficacy of this treatment. This suggests the need for novel therapeutic approaches that attempt to reduce the dose and frequency of treatment administration, improving patient compliance, and reducing costs. In this context, the use of novel adjuvants has been proposed and, in recent years, biomedical applications using nanoparticles have been exploited in the attempt to find formulations with improved stability, bioavailability, favorable biodistribution profiles, and the capability of targeting specific cell populations. In this article, we review some of the most relevant regulatory aspects and challenges concerning nanoparticle-based formulations with immunomodulatory potential, their related immunosafety issues, and the nature of the nanoparticles most widely employed in the allergy field. Furthermore, we report in vitro and in vivo data published using allergen/nanoparticle systems, discuss their impact on the immune system in terms of immunomodulatory activity and the reduction of side effects, and show that this strategy is a novel and promising tool for the development of allergy vaccines. Keywords: allergy, nanocarriers, immunotoxicity, immune modulation, immunotherapy, allergens